2020
DOI: 10.19173/irrodl.v21i4.4834
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Technology Acceptance Scale for Learning Mathematics: Development, Validity, and Reliability Studies

Abstract: The purpose of this study is to develop a valid, reliable, and useful scale to measure high school students’ levels of acceptance of mobile technologies in learning mathematics based on the second version of the unified theory of acceptance and use of technology (UTAUT2) model. The study was designed based on a sequential exploratory mixed-method research design. To this end, both qualitative (interviews with students, review of literature, and expert panel evaluation) and quantitative procedures (Lawshe conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…On the other hand, students' readiness for flipped classrooms is also considered important in their acceptance of flipped classrooms (Hao, 2016b). Açıkgül and Fırat (2023) also determined that secondary school students' readiness for flipped mathematics classrooms was at a good level.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, students' readiness for flipped classrooms is also considered important in their acceptance of flipped classrooms (Hao, 2016b). Açıkgül and Fırat (2023) also determined that secondary school students' readiness for flipped mathematics classrooms was at a good level.…”
Section: Discussionmentioning
confidence: 99%
“…Confirmatory Factor Analysis (CFA) results showed that the 6-factor structure was confirmed in a different study group. Cronbach's alpha and Composite Reliability Coefficients showed that the scores obtained from the scale were reliable (Açıkgül & Fırat, 2023).…”
Section: Flipped Mathematics Classroom Acceptance Scalementioning
confidence: 94%
See 1 more Smart Citation
“…The purpose of this research was to improve teaching and learning mathematics in higher education in Indonesia. One of the issues that have been encountered in education in Indonesia are the low level of students' engagement in learning mathematics (Açıkgül & Şad, 2020(Açıkgül & Şad, , 2021Casinillo et al, 2020;Fuentes-Cabrera et al, 2020;Mainali, 2021;Mazana et al, 2019;Mulenga & Marbán, 2020;Rohaizati, 2020). As a mathematics lecturer at State University of Padang, author also found that this issue have become major problems of my teaching practice.…”
Section: Introductionmentioning
confidence: 96%
“…Many new mathematical tasks can appear in this mobile learning context. They offer new possibilities for accessing mathematics knowledge and skills in a manner more exciting and suitable for children born in the tech boom (Acikgul & Sad, 2020). Thus, teaching mathematics in the 21 st century can overcome the constraints of traditional teaching in the previous centuries, for example, learning space, time, interaction, and connection (Meletiou-Mavrotheris et al, 2019).…”
Section: Introduction From Mobile Device To Mobile Learningmentioning
confidence: 99%